2020
DOI: 10.3390/cancers12082057
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Tumor Microenvironment in Neuroblastoma: Recent Advances and Future Directions

Abstract: Neuroblastoma (NB) is the most common pediatric tumor malignancy that originates from the neural crest and accounts for more than 15% of all the childhood deaths from cancer. The neuroblastoma cancer research has long been focused on the role of MYCN oncogene amplification and the contribution of other genetic alterations in the progression of this malignancy. However, it is now widely accepted that, not only tumor cells, but the components of tumor microenvironment (TME), including extracellular matrix, strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 205 publications
(261 reference statements)
0
43
0
Order By: Relevance
“…39 Targeting the TME along with tumor cells has been reported beneficial to a subgroup of high-risk NB patients. 40 As one of the major components belonging to the innate immune system, reactivating TAMs is necessary for reversing immune suppressive state and stimulating immune defense to exert tumoricidal function. Our data revealed that CD209 + CD36 + TAMs were more existed in the advanced stage of NB, while CD80 + CCR7 + TAMs as well as CD14 + CD16classic monocytes were more existed in tissues and PBMCs of early-stage NB, indicating the tumor-inhibiting and tumor-promoting TME in early and advanced NB environment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…39 Targeting the TME along with tumor cells has been reported beneficial to a subgroup of high-risk NB patients. 40 As one of the major components belonging to the innate immune system, reactivating TAMs is necessary for reversing immune suppressive state and stimulating immune defense to exert tumoricidal function. Our data revealed that CD209 + CD36 + TAMs were more existed in the advanced stage of NB, while CD80 + CCR7 + TAMs as well as CD14 + CD16classic monocytes were more existed in tissues and PBMCs of early-stage NB, indicating the tumor-inhibiting and tumor-promoting TME in early and advanced NB environment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Survival varies from nearly 100% for low-risk patients to less than 40% in the high-risk group. Their current treatment combines surgery, chemotherapy, radiation, and immunotherapy [ 104 ].…”
Section: Antiangiogenics and Neuroblastomamentioning
confidence: 99%
“…High-risk neuroblastomas are characterized by being very aggressive and have a highly vascular, angiogenic, hypoxic, and immunosuppressive TME [ 104 , 105 , 106 ]. They also express large amounts of VEGF, PlGF, FGF, PDGF, and endoglin [ 104 , 107 , 108 , 109 , 110 , 111 ], so some antiangiogenics against these targets have been used in patients and preclinical models of neuroblastoma.…”
Section: Antiangiogenics and Neuroblastomamentioning
confidence: 99%
“…These extracranial tumors commonly arise in and around the adrenal glands and are rare in kids older than 10 years of age [1,2] The amplification of MYCN oncogene is frequently observed in NB tumors and despite intensive multimodal treatments, which include chemotherapy, radiotherapy, anti-GD2 immunotherapy, and stem cell transplant, the overall survival of patients diagnosed with high-risk disease is less than 50%. The infiltration and accumulation of immunosuppressive myeloid cells, specifically myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM) in NB tumors, diminish effective antitumor immune responses, which leads to failure of immunotherapy and other conventional therapies in this childhood cancer [3][4][5].…”
Section: Introductionmentioning
confidence: 99%